A comparative analysis of Twitter users who tweeted on psychology and political science journal articles - Zhou, Yanfen (2018)
As Web 2.0 is changing the way of scholarly discussion and the measurements of journal articles impact, altmetrics have garnered much attention in recent years. Altmetrics measure the scholarly impact of journal articles based on how a research study is obtained, read, discussed, shared, and recommended on social media platforms among a variety of audiences. The purpose of this study is to understand the similarities and differences between the Twitter users who tweet on journal articles in psychology and political science disciplines. The data for this study was collected from Web of Science, Altmetric.com and Twitter. A total of 91,826 tweets with 22,541 distinct Twitter user profiles for psychology discipline and 29,958 tweets from 10,478 distinct Twitter for political science discipline were used for analysis. The demographics analysis include gender, geographic location, individual or organization user, academic or non-academic background, psychology/political science domain knowledge background. A machine learning approach using Support Vector Machine was introduced for user classification based on the Twitter user profile information. Latent Dirichlet Allocation (LDA) topic modelling was used to discover the topics that the users discussed from the tweets. Results show that the demographics of Twitter users who tweeted on psychology and political science are significantly different. A higher percentage of female Twitter users are involved in the discussion of journal articles in psychology than in political science. The percentage of Twitter users from Europe who tweeted on journal articles in political science is higher than that in psychology as the political science tweets topics are more about Europe. There are 20.7% of more organization users who tweeted on journal articles in psychology than political science. The percentage of non-academic Twitter users tweeted on journal articles is higher in psychology than in political science. It was also identified that the percentage of Twitter users who have the domain knowledge in political science is twice of that in psychology. Tweets on journal articles in psychology reflect the impact of scientific research finding on general public better than political science. The journal articles of psychology discipline attract more attention from general public than those of political science discipline.